If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4x + 4 = 40 Reorder the terms: 4 + 8x + 4x = 40 Combine like terms: 8x + 4x = 12x 4 + 12x = 40 Solving 4 + 12x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 12x = 40 + -4 Combine like terms: 4 + -4 = 0 0 + 12x = 40 + -4 12x = 40 + -4 Combine like terms: 40 + -4 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| 1.03x-4=-2.15+8.72 | | 2=6+a/2 | | 3x+6=2x+7-15x | | -5y-10=-16 | | 6-8x=7x-9x-30 | | -2(b+6)=-4 | | 3x+6=2x+6-15x | | 3x+6=2x+5-15x | | D+8/3 | | 3x+6=2x+4-15x | | 3x+6=2x+4-12x | | -4/7-(-2/7) | | 3(2x+5)=5(x+10) | | 5t+2=0.5(10t+4) | | 3x+6=2x+4-7x | | 3-2n=31+2n | | 3x+6=2x+4-5x | | -2(b+6)=4 | | 3x+6=2x+4-3x | | 5a=0.65 | | -3/4=k/16 | | -c+5=2c-4 | | 3x+6=2x+4-2x | | 3x+6=2x-4-2x | | 3x+6=2x-1-2x | | 2m+8+2m=12 | | 4x+81+0.5=360 | | n-6/3=-15 | | 3x+6=2x-1+25x | | 3x+6=2x-1+20x | | -12=(6x+27) | | 3a-1=-1 |